Reconceiving the closed approach in unilateral cleft lip rhinoplasty: An objective evaluation of 64 consecutive cases - Chirayu Parwal; Lalit Choudhary; Anurag Pandey; Shiv Shankar Saha; Vivek Kumar (Wolters Kluwer Medknow Publications, 2020)
Introduction: The cleft lip nose has been the classical case of an unsolved mystery in the history of plastic surgery. As Kernahan aptly stated, "a repaired cleft is revealed more by the associated nasal deformity than by the repair line." Cleft lip nasal deformity becomes a surgical challenge due to various reasons: 1. Wide variation in clinical presentation, requiring a host of surgical techniques. 2. Deformity may be quite asymmetric, making correction difficult. 3. Patients might have undergone several previous operations, which lead to scarring. Aim: We aim to assess the surgical outcome of the closed approach of unilateral cleft lip nose deformity correction. Methodology: We perform the cleft lip nose correction with the primary cleft repair as well as a secondary rhinoplasty in preschool age group and adults depending on the esthetic concerns. Our approach is the closed (endonasal) rhinoplasty technique to dissect the slumped alar cartilage of its soft-tissue attachments and cutaneous skin flap and reshape and reposition it with the help of sutures inserted percutaneously. Results: We have evaluated our results by comparing the pre- and post-operative photographs in standard views and represented the correction of several esthetic nasal parameters with a simple numerical rating. We have compiled the overall result by taking into account the collective numerical ratings at 6 months of follow-up. Our results of primary rhinoplasty ranked in the "good" or "excellent" category in 85% of the cases while it was "fair" or "good" in 82% of the secondary rhinoplasties. Conclusion: We conclude that the closed rhinoplasty is less invasive, takes less surgical time, avoids tedious dissection, gives better on table predictability of the outcome, and shortens postoperative recovery and tissue healing, providing a stable and acceptable result.